Pathogenic Variant in ACTB, p.Arg183Trp, Causes Juvenile-Onset Dystonia, Hearing Loss, and Developmental Delay without Midline Malformation. (12th April 2017) - Conboy, Erin; Vairo, Filippo; Waggoner, Darrel; Ober, Carole; Das, Soma; Dhamija, Radhika; Klee, Eric W.; Pichurin, Pavel
Abstract : ACTB encodes the β -actin, and pathogenic variations in this gene have typically been associated with Baraitser-Winter cerebrofrontofacial syndrome, a congenital malformation syndrome characterized by short stature, craniofacial anomalies, and cerebral anomalies. Here, we describe the third case with the p.Arg183Trp variant in ACTB causing juvenile-onset dystonia. Our patient has severe, intractable dystonia, developmental delay, and sensorineural hearing loss, besides hyperintensities in the caudate nuclei and putamen on the brain MRI, which is a distinct but overlapping phenotype with the previously reported case of identical twins with the same alteration in ACTB .